Separation/fractionation of triglycerides in terms of fatty acid constituents in palm kernel oil using supercritical CO2 - Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Abd Kadir, Mohd Omar (Elsevier Inc., 2006)
Separation of triglycerides in terms of fatty acid constituents in palm kernel oil (PKO) from dehulled ground palm kernel using supercritical carbon dioxide (SC-CO2) as a solvent at 40 and 80 ◦C and pressures of 20.7, 27.6, 34.5, 41.4 and 48.3MPa was studied. The extraction was continuous and PKO was fractionated into four fractions. Triglycerides with differing fatty acid contents of caprylic (C8), capric (C10), lauric (C12), myristic (C14), palmitic (C16), stearic (C18:0), oleic (C18:1) and linoleic (C18:2) acid were separated in different percentages in different fractions. About 70% of PKO comprises triglycerides with C8–C12 fatty acids and these fatty acids were mostly extracted in fractions 1and 2. As a result, higher yields were observed in these fractions, especially at pressures higher than 27.6MPa. The C16 and C18:2 components were extracted in fractions 3 and 4. These triglycerides form only a part of the remaining 30% of the fatty acid composition of PKO, hence the evidently diminishing yield in the later fractions. However, the compositions were found to be statistically significant for higher pressures and fraction times according to the type of fatty acid constituents.